EULAR recommendations for the non-pharmacological core management of hip and knee osteoarthritis: 2023 update - Moseng, Tuva; Vliet Vlieland, Theodora P M; Battista, Simone; Beckwée, David; Boyadzhieva, Vladimira; Conaghan, Philip G; Costa, Daniela; Doherty, Michael; Finney, Andrew G; Georgiev, Tsvetoslav; Gobbo, Milena; Kennedy, Norelee; et al. (Annals of the rheumatic diseases, 2024)
IntroductionHip and knee osteoarthritis (OA) are increasingly common with a significant impact on individuals and society. Non-pharmacological treatments are considered essential to reduce pain and improve function and quality of life. EULAR recommendations for the non-pharmacological core management of hip and knee OA were published in 2013. Given the large number of subsequent studies, an update is needed.MethodsThe Standardised Operating Procedures for EULAR recommendations were followed. A multidisciplinary Task Force with 25 members representing 14 European countries was established. The Task Force agreed on an updated search strategy of 11 research questions. The systematic literature review encompassed dates from 1 January 2012 to 27 May 2022. Retrieved evidence was discussed, updated recommendations were formulated, and research and educational agendas were developed.ResultsThe revised recommendations include two overarching principles and eight evidence-based recommendations including (1) an individualised, multicomponent management plan; (2) information, education and self-management; (3) exercise with adequate tailoring of dosage and progression; (4) mode of exercise delivery; (5) maintenance of healthy weight and weight loss; (6) footwear, walking aids and assistive devices; (7) work-related advice and (8) behaviour change techniques to improve lifestyle. The mean level of agreement on the recommendations ranged between 9.2 and 9.8 (0–10 scale, 10=total agreement). The research agenda highlighted areas related to these interventions including adherence, uptake and impact on work.ConclusionsThe 2023 updated recommendations were formulated based on research evidence and expert opinion to guide the optimal management of hip and knee OA.